English-Arabic Dictionary of Accounting and Finance (Book). - Meyer, Philip E.; Tawfik, Mohamed Sherif (The Accounting Review, 1983)
Abstract Reviews the book "English-Arabic Dictionary of Accounting and Finance," by Adnan Abdeen.